Implementasi Manajemen Pendidikan Karakter dalam Pembinaan Akhlak Peserta Didik di MIS Nurul Iman Gebang - Hambali Hambali; Ahmad Zaki; Khairani Sakdiah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyse the implementation of character education management in fostering students' morals at MIS Nurul Iman Gebang. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that: (1) Planning involves the formulation of lesson plans and educational programs that include goals, policies, methods, and directed procedures; (2) Organising is done through the division of tasks and time, as well as the placement of educators according to expertise to ensure output according to the institution's goals; and (3) Implementation includes habituation of religious values, strengthening of commendable behaviour, and practical activities that support the formation of noble morals. (4) Evaluation is done by supervising implementation in the classroom, providing feedback to educators, and interviewing student guardians to ensure conformity with the institution's goals. This study confirms the importance of character education management in shaping students' good morals through collaboration between institutions, educators and families.